POSSIBILITIES OF BACTERIOPHAGE THERAPY IN THE TREATMENT OF PATIENTS WITH COMPLICATED URINARY TRACT INFECTION - S. N. Zorkin; D. S. Shakhnovskiy (Union of pediatricians of Russia, 2013)
Study aim: evaluation of efficacy of a range of bacteriophages in children with urinary tract infection caused by a urologic pathology. Study participants and methods. The study involved 331 children with a urologic pathology manifesting itself with disturbed urodynamics and secondary urinary tract infection. 159 children received operative treatment; the other 172 children were subjected to conservative treatment methods. The patients were divided into 4 groups: (I) operative treatment + antibiotic therapy, (II) operative treatment + antibiotic therapy + bacteriophage therapy, (III) only antibiotic therapy, (IV) antibiotic therapy + bacteriophage therapy. Bacteriological urine culture was conducted. The revealed microbes were differentiated using 27 biochemical tests with subsequent determination of microbial sensitivity to antibacterial drugs. The trials were conducted at admission to inpatient hospital, 7-14 days after and 6-12 months after. Results. Enterobacteriaceae family pathogens (Escherichia coli) were prevalent at admission - 63.7%; Klebsiella spp. was the second - 15.2%; Pseudamonas aeruginosae - 9.2%, Enterococcus spp. and Enterobacter spp. - 6.0% each. Bacteriuria rate in the group I children was 38.5% at admission, 62.6% 7-14 days after and 32.5% 6-12 months after. There were no differences in preoperative and early postoperative periods in the group II children, but there was a tendency to bacteriuria rate reduction. The combined use of an antibiotic and a bacteriophage in children subjected to operative treatment resulted in an almost double bacteriuria rate reduction in comparison with a group of children who received only antibacterial therapy without an operation (5.8 and 13.7%, respectively). Differences in urine microfloral species composition in the children of groups III and IV indicate the reduction in hospital flora pathogens, especially in case of the combined use of an antibiotic and a bacteriophage: normalization of urine analyses within the first month in 81.3% of cases, remission duration longer than 6 months in 92.0% of cases. Conclusions: the use of bacteriophages appears to be prospective as antibiotic resistance of causative agents of various infections and of their complications increases.